Effect of Temperature and Drying Time on Angiostensin Converting Enzyme (ACE) Inhibitor and Antioxidant Activity of Soybean (Glycine max L.)- Jackbean (Canavalia ensiformis L.) Mix Grains Tempeh Flour - Andriati Ningrum; Sri Anggrahini; Diah Ayu Puspasari (Indonesian Food and Nutrition Progress, 2021)
The increase of hypertension sufferers encourage the development of functional foods. The presence of tempeh mixed grains of soybean and jackbean contains bioactive peptides as antihypertensive and antioxidant agents encourage the development of functional food such as tempeh flour of mixed grains. The research was aimed to investigate the effect of temperature and drying time on functional properties, asam amino acid profile, and isoflavone compounds. The different drying temperatures (50 oC and 70 oC) and drying time  (6; 8; and 10 h) were applied on soybean and jackbean tempeh (1:1) w/w) for making the mixed grains tempeh flour. The Angiotensin Converting Enzyme (ACE) inhibitor activity, antioxidant activity, and total phenolic, amino acids profile, and isoflavone content of the flour were analyzed. The result showed that the best tempeh flour of mixed grains was obtained by drying at 70°C for 8 h with ACE inhibitor activity of 86.04%, antioxidant activity of 55.34% and total phenolic of 3.98 mg/g DB. This flour contained amino acids related to ACE-Inhibitor peptide precursors (glutamic acid and leucine), antioxidant peptide precursors (phenylalanine and histidine) as well as isoflavone compounds (daidzein and genistein). This finding reveals that drying temperature and time affected the functional properties, amino acids profile and isoflavone compounds.